Estrategias de difusión para acciones de la responsabilidad ambiental como diferenciador de las organizaciones. Caso: Aseguradora del Sur - Cobo Callejas, Luisa Fernanda (2016)
Environmental responsibility is raging within society and imposes an interest in the entire population because of concerns about global warming. This book addresses this issue with the Aseguradora del Sur, highlighting that when the environmental actions developed by the company are properly communicated, an important differentiator is generated in the competitive market of the insurance field. The research was able to identify that the company does not communicate the ESR (environmental social responsibility) actions that it develops. This data was obtained thanks to a quantitative and qualitative study utilizing surveys, interviews and observation sheets to analyze the perception of key stakeholders, which, according to the model proposed by Farré (2012), are employees, customers, suppliers and competitors. They reported that it would be imperative to be aware and participate in these ESR actions. Therefore, a proposal called "Commitment to Asegsur" was introduced, seeking to take advantage of the environmental projects that are carried out to create a better image, strengthen ties with those involved, and especially to distinguish the company by giving it a competitive advantage over the rest. This is an essential study, not only to generate this environmental issues differentiator, but also to understand that proper communication can generate significant results in different areas of the organizations.